Spirituality: The Core Of Attitude With Social Awareness - Halim Purnomo; Firman Mansir (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The individuals’ spiritual step is tightly enough with attitude and personality. The better of the spiritual, the better of the habit and personality are. This can be caused by defining the life in which there are running to always orientate on their process and purpose of life, it is achieving a better life. This article used library research from previous studies which explored the changing attitude and social awareness of human on spiritual value. This is aimed to explain the core of the changing human’s attitude with social awareness through the spiritual dimension. Then, to support the explanation, this article is completed with academic debate on the involvement spiritual dimension toward the changing human’s attitude and social awareness. In this article, it will be explained that the changing of human attitude and social awareness that will directly be guided to the better one and always coupled with the spiritualist step through the dimension.